Calibrating Codes Safety Factors for Different Life Cycles - Proposed Simplified Procedure - Shamir, Eliezer (Advanced Aspects of Engineering Research Vol. 13, 2021)
In light of a 120-year life cycle, a simpler method for calibrating code safety factors was used in the updating of the upgraded Israeli Code specifications for aseismic construction of bridges. Structures are often assumed to be planned for a 50-year life cycle, whereas unique or critical infrastructure facilities should be designed for longer life cycles. Aside from issues of reliability and maintenance, this also entails the need to cover the risk of exceeding characteristic design live loads for a prolonged period while maintaining the same standards of agreed risk assumed by various codes as good enough for the typical 50-year life cycle. Given that these structures are designed using design methods, formulations, material characteristic strengths, and partial safety factors in accordance with existing codes, scaling of partial safety factors, or alternatively an additional "compensating" factor, is needed. This proposed simplified procedure to arrive at a reasonable calibration of code safety factors, based upon structural reliability considerations, is presented.